Transmastoid Repair of Spontaneous Cerebrospinal Fluid Leaks - Perez, Enrique; Carlton, Daniel; Alfarano, Matthew; Smouha, Eric (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Determine the efficacy of using a purely transmastoid approach for the repair of spontaneous cerebrospinal fluid (CSF) leaks and further elucidate the relationship of elevated body mass index (BMI) and skull base thickness in our patient population.Method We conducted a retrospective chart review of patients treated for spontaneous temporal bone CSF leaks at our tertiary care institution from the years 2006 to 2015. Cases were categorized as primary or secondary. We analyzed success rates, length of stay, use of lumbar drains, BMIs, and rates of meningitis. Skull base thickness was compared with BMI in each case.Results We identified 26 primary operations for spontaneous CSF leaks and 7 secondary operations. Twenty-three of 33 repairs were performed via the transmastoid approach alone with an 87% success rate (20/23). Of the10 repairs including a middle cranial fossa (MCF) or combined MCF-transmastoid approach, 2 failed for an 80% success rate (8/10). Five transmastoid repairs underwent placement of a lumbar drain versus all 10 repairs employing an intracranial exposure. Average length of stay for those undergoing a transmastoid approach (1.7 days) was significantly shorter than for patients undergoing a MCF repair (6.3 days). Four patients presented with meningitis. Average BMI was 35.3. No correlation was established between BMI and skull base thickness (R2 = 0.00011).Conclusion The transmastoid approach is effective in the majority of cases and prevents the need for an intracranial operation, resulting in lower morbidity and a shorter length of stay. We believe that this is the preferred primary approach in most patients with spontaneous CSF leaks.
Keywords: encephalocele; middle cranial fossa; body mass index; length of stay; lumbar drains; transmastoid; spontaneous cerebrospinal fluid leak